Performance and fatigue patterns in elite cyclists during 6 h of simulated road racing - Klaris, M. B.; Cubel, C.; Bruun, T. R.; Stampe, D.; Rørvik, S.; Fischer, M.; Bonne, T.; Christensen, P. M.; Piil, J. F.; Nybo, L. (Scandinavian Journal of Medicine & Science in Sports, 2024)
Fatigue resistance is vital for success in elite road cycling, as repeated, intense efforts challenge the athletes' ability to sustain peak performance throughout prolonged races. The present study combined recurrent performance testing and physiological measures during 6 h simulated racing with laboratory testing to investigate factors influencing fatigue resistance. Twelve male national elite cyclists (25 ± 3 years; 76 ± 6 kg and VO2max of 5.2 ± 0.5 L/min) completed incremental power and maximal fat oxidation tests. Subsequently, they underwent field testing with physiological measures and fatigue responses evaluated through peak sprint power and 5 km time trial (TT) testing after 0, 2, 4, and 6 h of exercise. Peak power declined from 1362 ± 176 W in first sprint to 1271 ± 152 W after 2 h (p < 0.01) and then stabilized. In contrast, TT mean power gradually declined from 412 ± 38 W in the first TT to 384 ± 41 W in the final trial, with individual losses ranging from 2% to 14% and moderately correlated (r2 = 0.45) to accumulated exercise time above lactate threshold. High carbohydrate intake (~90 g/h) maintained blood glucose levels, but post-TT [lactate] decreased from 15.1 ± 2 mM to 7.1 ± 2.3 mM, while fat oxidation increased from 0.7 ± 0.3 g/min at 0 h to 1.1 ± 0.1 g/min after 6 h. The study identifies fatigue patterns in national elite cyclists. Peak sprint power stabilized after an initial impairment from 0 to 2 h, while TT power gradually declined over the 6 h simulated race, with increased differentiation in fatigue responses among athletes.